Praxis and Religious Authority in Islam: The Case of Ahmad Dahlan, Founder of Muhammadiyah - Kim, Hyung-Jun (Studia Islamika, 2010)
The purpose of this paper is to examine the role of praxis in the formation of religious authority. Although not fully acknowledged in Islam, the separation of religious from non-religious domains has become sharper and more clearly discernable in modern society. Accordingly, it is relevant to ask how praxis in the politico-economic and socio-cultural domains is evaluated in Islamic terms and what roles it plays in accessing religious legitimacy and leadership. The focus of this study is on Ahmad Dahlan, the founder of an Islamic mass-organization in Indonesia, the Muhammadiyah. Examination of his background reveals that he was not equipped with the traditional sources of authority.DOI: 10.15408/sdi.v17i1.468